Photo-healable ion gel with improved mechanical properties using a tetra-arm diblock copolymer containing azobenzene groups. (5th November 2015) - Ma, Xiaofeng; Usui, Ryoji; Kitazawa, Yuzo; Kokubo, Hisashi; Watanabe, Masayoshi
Abstract: Photo-healable ion gels with improved mechanical properties are demonstrated using a tetra-arm diblock copolymer (A(B)4 ) containing azobenzene groups. Physical ion gels were prepared by self-assembly of A(B)4 in a hydrophobic ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate ([C4 mim]PF6 ), where A block is the ionic liquid-compatible tetra-PEG, and B block is the thermo-/photo-responsive random copolymer of 4-phenylazophenyl methacrylate and N -isopropylacrylamide (P(NIPAm- r -AzoMA)). The A(B)4 ion gels have a higher modulus and fewer network defects than the triblock copolymer (A(B)2 ) ion gel (A block is PEG; B block is P(NIPAm- r -AzoMA)). Self-standing A(B)4 ion gels were obtained at a lower polymer concentration than A(B)2 ion gels in [C4 mim]PF6 . The A(B)4 /[C4 mim]PF6 and A(B)2 /[C4 mim]PF6 binary systems exhibit low-temperature gel-states and high-temperature sol-states. The gel-to-sol transition temperature also depends on the photoisomerization state of the azobenzene moiety in the polymers. It is confirmed that photo-induced sol–gel transition is reversible at a suitable temperature. Photo-healable ion gels are demonstrated using the photo-induced reversible sol–gel transition, where damaged regions are UV-light-irradiated to induce the gel-to-sol transition then visible-light-irradiated to heal the gels by the sol-to-gel transition. Remarkable photo-healing efficiency in terms of the mechanical properties is realized by this procedure. Graphical abstract: Highlights: We compared tetra-arm diblock copolymer (A(B)4 ) ion gels with triblock copolymer (A(B)2 ) ion gels. A(B)4 ion gels have higher mechanical properties than A(B)2 ion gels. A(B)4 ion gels have more uniform network structure than A(B)2 ion gels. A(B)4 ion gels show reversible photo-induced sol-gel transition at certain temperatures. Photo-healable ion gel with higher photo-healing efficiency can be realized.